Asas Hukum Perdata sebagai Dasar Perlindungan Hukum dalam Perjanjian Pengiriman Barang - Krisno Aji (Jurnal Hukum Lex Generalis, 2025)
The existence of an agreement that creates a contractual obligation subsequently imposes obligations that must be fulfilled by the parties, or what can be called performance. Performance arising from a contractual obligation must be carried out to prevent harm to the other party. This study aims to further examine the role of civil law principles and principles of transportation law in the delivery of goods. It is important for the parties to understand that their respective rights and obligations are regulated by applicable legal regulations.